Capital Budgeting Analysis Of Investment Project Feasibility in PT Integra Indocabinet TBK - Adetia Wardani; Wahyudiono Wahyudiono (Journal of World Conference (JWC), 2020)
This research is a case study conducted in one of the property companies in Sidoarjo, East Java, namely PT Integra Indocabinet Tbk ,. Based on secondary data, PT Integra Indocabinet has increased sales and profits from 2014 - 2018. Therefore, the owners want to expand their expansion by adding new factory facilities so they can get more optimal profits and can increase exports abroad. The research aims to provide assistance in the form of suggestions for decision making between feasible or not worthy of the investment carried out. Based on the calculation, obtained an NPV value of 195,510,594,699 ? 0 which means it is feasible to run, an IRR of 22%> hurdle rate (10%) which means it is feasible to run; Payback Period is 4 years 3 months> 5 years which means it is feasible to be implemented; The Profitability Index is 1.98> 0, which means it's worth running. The results of the analysis show that using Capital Budgeting techniques can be seen that investment decisions for expansion are feasible.